Influence of Micellar Non-Ionic Surfactant Solutions in the Release of Sorbed Hydrophobic Polycyclic Aromatic Hydrocarbons in Soil Slurry - A.M. Msagati, Titus; B. Mamba, Bhekie (Asian Journal of Chemistry, 2012)
In this study, we have investigated the efficiency of three micellar non-ionic surfactants in the solubilization of hydrophobic polycyclic aromatic hydrocarbons mainly, naphthalene, phenanthrene and pyrene. The non-ionic surfactants tested include the Tween 20, Tween 80 and Triton X-100. The critical micelle concentration (CMC) of all the surfactants was investigated by using a plot of surface tensions of surfactants versus log of their respective concentrations. The results show that Tween 80 performed better than the other three surfactants in the dissolution of polycyclic aromatic hydrocarbons. The gas chromatography coupled to a mass spectrometer was used for the separation and detection of the analytes.